Plant diversity and energy potency of community forestin East Kalimantan, Indonesia: Searching for fast growing wood species for energy production - RUDIANTO AMIRTA; YULIANSYAH YULIANSYAH; EDDY MANGOPO ANGI; BAMBANG RUDY ANANTO; BUDHI SETIYONO; MUHAMMAD TAUFIQ HAQIQI; HELMI ALFATH SEPTIANA; MARTER LODONG; RIZKI NUR OKTAVIANTO (Nusantara Bioscience, 2016)
Abstract. Amirta R, Yuliansyah, Angi EM, Ananto BR, Setiyono B, Haqiqi MT, Septiana HA, Lodong M, Oktavianto RN. 2016. Plant diversity and energy potency of community forest in East Kalimantan, Indonesia: Searching for fast-growing wood species for energy production. Nusantara Bioscience 8: 22-30. Nowadays, there is an increasing interest in intensifying the production and use of biomass to replace fossil fuels for the production of heat and electricity, especially for a remote area that generally abundance with the wood biomass resources including in East Kalimantan, Indonesia. In this work, diversity of plant species that commonly grows in community forest area of East Kutai District, East Kalimantan, Indonesia had been studied to point out their energy potency to be used as biomass feedstock for the electricity generated. Diversity of plant species in the community forest was evaluated by making 13 sampling plots with 20mx20m size approximately. Concurrently, the energy properties of plant biomass such as proximate and ultimate compositions were also analyzed using ASTM methods. Results showed that more than 30 species of tropical trees and wood shrubs were grown in the community forest. The presence of them was classified into two different growths of origins: natural and artificial plantation, and also three different categories of plant resources: tree species from logged-over forest, commercial fast-growing plant tree species for the fiber production and wood shrubs. The highest dominancy and productivity was found in Paraserianthes falcataria (L.) Nielsen since the wood biomass was artificially planted for commercial purposes. Among the 31 plant species analyzed we found the highest energy potency was obtained from Cratoxylum cochinchinense (Lour.) Blume that produced 3.17 MWh/ton, and the lowest was from Trema orientalis (L.) Blume 0.97 MWh/ton. The wood shrubs species such as Vernonia amygdalina Delile., Piper aduncum L., Gliricidia sepium (Jacq.) Kunth ex Walp., Calliandra calothyrsus Meissner., Bridelia tomentosa Blume, Vitex pinnata L., Vernonia arborea Buch.-Ham. and Bauhinia purpurea var. corneri de Wit. were suitable to be used as sustainable feedstocks for the electricity generated and promising to be developed as energy plant species in the future using Short Rotation Coppice system (SRC).